2016
DOI: 10.1016/j.celrep.2016.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Negative Selection and Chromosome Instability Induced by Mad2 Overexpression Delay Breast Cancer but Facilitate Oncogene-Independent Outgrowth

Abstract: SummaryChromosome instability (CIN) is associated with poor survival and therapeutic outcome in a number of malignancies. Despite this correlation, CIN can also lead to growth disadvantages. Here, we show that simultaneous overexpression of the mitotic checkpoint protein Mad2 with KrasG12D or Her2 in mammary glands of adult mice results in mitotic checkpoint overactivation and a delay in tumor onset. Time-lapse imaging of organotypic cultures and pathologic analysis prior to tumor establishment reveals error-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 52 publications
7
103
0
1
Order By: Relevance
“…4b and 5a). These two mutually exclusive states, which were recently observed in a pan-cancer genomic analysis of metastatic tumors 41 , likely account for the reversibility in chromosome missegregation rates seen in primary tumors and metastases, and provide an explanation for the negative effect of aneuploidy during early tumorigenesis 40,42 . It also leads us to suggest that CIN drives the subset of human metastases characterized by EMT and inflammation 41 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…4b and 5a). These two mutually exclusive states, which were recently observed in a pan-cancer genomic analysis of metastatic tumors 41 , likely account for the reversibility in chromosome missegregation rates seen in primary tumors and metastases, and provide an explanation for the negative effect of aneuploidy during early tumorigenesis 40,42 . It also leads us to suggest that CIN drives the subset of human metastases characterized by EMT and inflammation 41 .…”
Section: Discussionmentioning
confidence: 67%
“…The emergence, and subsequent tolerance, of CIN represents an important bottleneck during tumor evolution 3840 . We found that CIN induces a transcriptional shift from a proliferative and highly metabolic state, ideally suited for primary tumor growth, to a mesenchymal state associated with upregulation of inflammatory pathways (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Even in a potentially permissible cellular environment lacking p53, there is strong evidence to show that induction of aneuploidy in diploid cells is associated with reduced fitness and delays tumor formation (Rowald et al 2016;Sheltzer et al 2016). Work in yeast and human cells shows that aneuploidy induces metabolic and proteotoxic stress, which translate into lower proliferation rates (Torres et al 2007(Torres et al , 2010Williams et al 2008;Oromendia et al 2012;Sheltzer et al 2012;Sheltzer 2013;Dürrbaum et al 2014).…”
Section: The Consequences Of Aneuploidymentioning
confidence: 99%
“…Importantly, CIN does not only seem to affect cancer growth, but also the ability of cancer to adapt and spread as transient CIN induction can lead to tumor recurrence. [97,98] In addition, CIN can facilitate metastasis, [99] lead to drug resistance [100] and lowers survival rate in patients. [101] However, to better understand which CIN rates in cancer drive further evolution toward therapy resistance and which CIN rates are toxic for tumor progression, we need better tools to quantify CIN rates in vivo.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 99%